Unraveling everyday heating practices in residential homes - Eon, Christine; Morrison, Gregory; Byrne, Joshua (Elsevier, 2017)
Recent research has found that low-emission buildings do not necessarily meet their full theoretical energy saving potential and one of the reasons for this discrepancy is related to occupancy. Inside the building, users interact with technologies and are influenced by everyday practice and subsequent behaviour. This research aims to unravel the layers of complexity in everyday practice with regards to heating and the use of renewable energy. For this purpose, ten Australian houses were established as embedded Living Labs and monitored for over a year. Results show that the studied households use climate control at different times of the day depending on lifestyle. However, individuals in the same household may have different heating practices according to motivations, attitudes and subjective norms. The combination of quantitative monitoring and qualitative assessments revealed that lifestyle, family structure, habits, comfort and the presence of renewable energy all impact on the frequency, timing and intensity of heating and cooling practice. This research provides a better understanding of intra-home and everyday practices, helping to inform the transition from energy efficient houses to energy efficient home systems.